The Aimless Life : Music, Mines, and Revolution from the Rocky Mountains to Mexico - Worcester, Leonard, Jr., 1863-1939 (Book collections on Project MUSE., 2021)
"The Aimless Life is a historical memoir that tells the story of Leonard Worcester, Jr. and provides a clear example of the capitalist development of the American West and borderlands regions in the second half of the nineteenth century and early twentieth century"--